A Customised Ocular Prosthesis for an Ocular Defect - Luthra, Reena; Kaur, Palwinder; Sharma, Puneet; Sharma, Anuradha (The Journal of Dentists, 2016)
The face is the first presentation of human expressions for communication in the society. Disfigurement of any part of the face leads to a crippled life manually, socially as well as psychologically. In recent years, rehabilitation of facial defects has seen a lot of advances in terms of technology and materials. Custom made prostheses have received good acceptance by patients due to improved esthetics and better retention. Ocular defects are being successfully restored by customized acrylic eyes. Prosthetic rehabilitation of the lost eye in a patient by custom made ocular prosthesis is discussed in this case report.